A Comprehensive Review on Down Syndrome Diagnosis and Associated Genes: Diagnosis of DS - Sattoju, Dr. Nithish (Clinical Medicine And Health Research Journal, 2023)
Down syndrome (DS) is an inherited genetic disease characterized with the trisomy of chromosome 21. The major clinical presentation of DS is intellectual disability which is seen among 12-15% of DS patients in the developed countries. Increased maternal age over 30 years increases the risk of having DS child. DS affects various organ systems causing cardiac disorders, GI abnormalities, hematological anomalies, endocrine disorders and skin diseases along with morphological anomalies of face, feet and hands. The current review aims at outlining the genes associated with cardiac, GI and hematological disorders seen in DS patients along with DS itself and also widely used diagnostic tools in identifying the disorder.